شرعنة مجموعات من السجلات الزلزالية الحقيقية لاستخدامها في التحليل الديناميكي لمنشآت واقعة في مدينة اللاذقية-سورية - حسن, نايل; جديد, سراج (Latakia University Journal -Engineering Sciences Series, 2017)
لم تعد الطريقة الستاتيكية المكافئة أو طيف الاستجابة؛ التي تستخدم عادة للتصميم الإنشائي لمعظم أنواع المنشآت التقليدية؛ من المنهجيات المفضلة في تصميم المنشآت الحديثة المعقدة التركيب والأداء خصوصا عند تعرضها لحمولات شديدة. ومن الناحية الأخرى أصبح التحليل الخطي و اللاخطي باستخدام السجل الزمني أداة عملية ومستخدمة على نطاق واسع، يعود ذلكللمتطلبات الزلزالية الجديدةإضافة للتطور والأداء العالي للحواسب، وأيضا بسبب الازدياد المستمر في قاعدة البيانات الخاصة بالحركات الأرضية القوية. لذلك أصبح استخدام وتقييس (معايرة) السجلات الحقيقية أحد أهم الأغراض الأساسية للأبحاث المعاصرة في هذا المجال.تأخذ معايير اختيار السجلات الزمنية بعين الاعتبار السمات الزلزالية لتلك السجلات كقوة الزلزال والمسافة عن البؤرة السطحية ومواصفات الموقع لأنها تؤثر على شكل طيف الاستجابة ومحتوى الطاقة ومدة الحركات الأرضية القوية، وبالتالي الطلب المتوقع على المنشأ. وبعد عملية اختيار السجلات الزلزالية الحقيقية يجب تقييسها لمطابقة شدة الزلزال المحتملة في الموقع. حيث تجرى عملية التقييس عادة باستخدام التقييس الموحد في مجال الزمن، وذلك ببساطة عن طريق تقییس السجلات الزمنية بتكبیرها أو تصغیرها بشكل موحد لتتم مطابقتها (بشكل متوسط)مع طیف الاستجابة الهدف ضمن المجال المحدد للدور بأفضل ما يمكن. إن عملية إيجاد معاملات التقييس لتأمين المطابقة الأفضل مع الطيف الهدف هي من مهام المهندس وهي عملية صعبة ومعقدة، لذلك قمناباستخدام الخوارزمية الجينيةفي إيجاد تلك المعاملات بهدف الحصول على أفضل النتائج.يعتبر إجراء تحليل لاخطي باستخدام السجل الزمني للحركات الأرضية المختارة و المعايرة نهجا تقليديا بهدف شرعنة النتائج من خلال تقييم انحراف وتغير الاستجابة الإنشائية. فهذا يثبت كفاية وفعالية الطرائق المستخدمة.قمنا في هذا البحث بتلخيص المنهجيات الخاصة بعمليات الاختيار والتقييس، وناقشنا معايير اختيار وتقييس السجلات الزمنية الحقيقية لإرضاء متطلبات الكود السوري. وتم توظيف إجراءات التقييس باستخدام الخوارزمية الجينية لتقييس عشرة مجموعات من السجلات، تتكون كل مجموعة من سبعة سجلات من السجلات الزمنية الحقيقية المتوفرة لهدف مطابقة الطيف التصميمي السوري. ثم قمنا بفحص السجلات الزمنية الناتجة ومقارنتها لتبيان مدى ملائمتها للاستخدام كتوابع تحريض في التحليل بالسجل الزمني لمنشآت الهندسة المدنية، من خلال التحليل باستخدام السجل الزمني لمنشآت وحيدة درجة الحرية بهدف فحص فعالية طريقة المعايرة المستخدمة في خفض التبعثر في الاستجابة الإنشائية. حيث تم تمثيل المنشآت وحيدة درجة الحرية باستخدام نماذج ثنائية الخطية الهستيرية (الإرجاعي)،من خلال افتراض خمسة أدوار ومعامل مطاوعة R=4.5 ونسبة صلابة ما بعد الخضوع α=3%وإجراء 700 عملية تحليل. وأخيرا تم عرض النتائج بدلالة الانتقالات اللدنة D.Structural design for seismic loading, which is traditionally done for most types of common structures by the means of equivalent lateral static loading or modal spectrum analysis, is no longer a preferred methodology for design of modern structures with complex topology and functionality under extreme loading scenarios. Nonlinear response history evaluation, on the other hand, is becoming a practical tool due to availability of high performance computing and recommendations of the new seismic guidelines, and due to the increase of available strong ground motion database.Therefor using and scaling real recorded accelerograms is becoming one of the most contemporary research issues in this field.Seismological characteristics of the records, such as earthquake magnitude, epicentral distance and site classification are usually considered in the selection of real records, as they influence the shape of the response spectrum, the energy content and duration of strong ground shaking, and therefore the expected demand on structures.After real seismic recordsselection it is necessary to scale these records to match the intensity of the earthquake expected for the site.Generally, scaling can be made by ground motions uniform scaling in time domain which is simply scaled up or down the ground motions uniformly to best match (in average)the target spectrum within a period range of interest. It’san engineer’sjob to find the best scaling factors to best match the target spectrum,which isa complextask,so we employed the Genetic Algorithm(GA) in finding them to achieve the best results.When testing the selected and scaled ground motions, it’s a standard procedure to use the nonlinear time history analysis to validate the results in terms of structural responses and their variation. this proves the efficiency of the presented procedure.In this study, basic methodologies for selecting and scaling strong ground motion time histories are summarized, the selection and scaling criteria of real time history records to satisfy the Syrian design code are discussed. The GA scaling procedures are utilized to scale 10 set of records, every set consists of seven records of available real records to match the Syrian design spectra. The resulting time histories are investigated and compared in terms of suitability as input to time history analysis of civil engineering structures,bymean of time history analyses of SDOF systems which are conducted to examine the efficiency of the scaling method in reducing the scatter in structural response. The nonlinear response of SDOF systems is represented by bilinear hysteretic model. Assuming 5 different Periods, yield strength reduction factor, R=4.5, 3% post-yield stiffness, a number of 700 runs of analysis are conducted. The results are described for elastic displacement D.